Direitos humanos e reforma agrária - Whitaker, Dulce Consuelo Andreatta [UNESP] (My University, 2011)
This paper focuses on the Agrarian Question and examines the emergence of human rights from a historical perspective. Great emphasis is placed on the right to life guaranteed by the State Constitutions of the Countries of the World that contained an elaborate Bill of Rights, providing strategies of territorial integration through agrarian reform, allowing landless to reside on and use land as a means to restore their dignity which they were assigned at birth, according to the Universal Declaration of Human Rights, although their rights have been usurped in the trajectories of their lives by social disruptions and exclusion. From this perspective, the agrarian reform might be understood in a way that allows settlers and people who live in rural areas to argue that the political process should be concerned with ensuring them equal rights taking into account all aspects of urban and social space.

O texto trata da Questão Agrária, à luz da emergência histórica dos Direitos Humanos. Argumenta então que o direito à vida, proclamada por todas as Constituições dos Estados de Direitos exige a integração dos despossuídos à terra de trabalho, via Reforma Agrária, como forma de restaurar-lhes a dignidade que lhes fora atribuída ao nascer, conforme a Declaração Universal dos Direitos Humanos e que lhes foi usurpada em trajetórias de vida cheias de rupturas e de exclusão social. Entender a Reforma Agrária por esse prisma permite a todos os assentados, bem como a todos os habitantes do campo, reivindicarem os direitos fundamentais concedidos aos habitantes da cidade e pensados sempre do ponto de vista do espaço social urbano.
Keywords: Agrarian Issue; Right to Life; Public Policies for the Rural Area; Questão Agrária; Direito à Vida; Políticas Públicas para a Zona Rural